CHILDREN’S EMPOWERMENT IN THE LITTLE PRINCE: A LITERARY ANALYSIS BASED ON ANSHORI’S FRAMEWORK - Ning Difani Wulan; Adam Anshori (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
Previous studies on Antoine de Saint Exupéry’s The Little Prince have predominantly focused on its symbolism and philosophical meanings, leaving the dimensions of children’s empowerment underexplored. Therefore, this study aims to examine how empowerment dimensions are depicted in The Little Prince, as the main character, through a multidimensional perspective. Employing a qualitative textual analysis design, this study adopts Anshori’s (2016) conceptualization of children’s empowerment focuses on the children’s thoughts, actions, and emotional experiences. The primary data source is the novella, focusing on narrative events and character interactions that illustrate empowerment. Within the literary analysis framework, the researcher served as the primary instrument. The findings show the character embodies existential empowerment beyond conventional child agency. The Little Prince demonstrates intellectual independence, responsibility, and emotional sensitivity, which collectively shape a multidimensional conception of empowerment. Furthermore, this study of children’s literature challenges the view that children are passive figures and highlights the text’s critique of adult rationalism and materialism. In doing so, it highlights the pedagogical significance of literary texts in fostering reflective, ethically grounded individuals.